SISTEM INFORMASI GEOGRAFIS PADA PEMETAAN PERSEBARAN LOKASI BANGUNAN PUSAT KESEHATAN MASYARAKAT, PUSKESMAS PEMBANTU, DAN PONDOK KESEHATAN DESA DI EMPAT KECAMATAN KABUPATEN TULUNGAGUNG - ABDULLOH, ABDI BURHANUDDIN (Universitas Negeri Surabaya, 2023)
Efforts aimed at developing health facilities contribute significantly to the realization of optimal public health outcomes. Ensuring easy access to healthcare services and focusing on quality improvement are crucial factors for successfully developing health facilities. The limited availability of information sources regarding these facilities necessitates acquiring data or information to ascertain their geographical locations and conditions. This final research project will present a diverse range of information sources pertaining to health facility buildings in the sub-districts of Karangrejo, Ngantru, Kedungwaru, and Kauman. Utilizing a Geographic Information System (GIS) as a visualization tool enables convenient access to transportation, supporting facilities, and travel distances to the desired destinations. Additionally, this study employs the nearest neighbour method to analyze the distribution patterns of puskesmas, pustu, and ponkesdes, including assessments of clustering and random or evenly distributed patterns, indicated by the T-value. The results obtained from the analysis of the distribution patterns using the nearest neighbour method for puskesmas, pustu, and ponkesdes buildings in the four sub-districts of Tulungagung Regency demonstrate consistent findings for puskesmas and pustu, revealing a dispersed distribution pattern. Meanwhile, the distribution pattern of ponkesdes buildings exhibits a random pattern in terms of their locations.